WEB PLACE NAME DICTIONARY IMPLEMENTATION USING TWITTER AS SOURCE TO DEVELOP TRAFFIC INFORMATION SYSTEM - Rachmad Akbar; Ari Wibisono; Petrus Mursanto (Jurnal Sistem Informasi, 2014)
Abstract Congestion is one of the severe problems that occurs in big cities like Jakarta, the center of the Indonesian government. One alternative solution to solve this problem is with a Traffic Information System which is easily accessible by the public. Twitter as a social media can be used as one of information source to develop the Traffic Information System. The most common problem in the processing of information on Twitter, especially in Indonesia, is the use of abbreviations and typographical error (typo). We propose an application of Web Place Name Dictionary in addressing abbreviations and typos in the name of the location contained on Twitter to develop a Traffic Information System. Three cases in find coordinate point in the street that derived from location name in Twitter can be handled through the proposed system. This system produces 90% accuration rate on 100 data set that obtained via @TMCPoldaMetro. This study only focus on the implementation of Web Place Name Dictionary method so we do not compare our system with the other methods.